Testing the Psychometric Properties of the Fear of Missing Out (FOMO) Instrument on Tiktok Users - Dinda Aziziyah Al Mufarida; Muflihatul Hidayah; Sigit Hendrawan Wicaksono; Rizky Putra Santosa (International Conference on Psychology and Education (ICPE), 2024)
This study aims to develop a measuring instrument for Fear of missing out (FOMO) behavior based on four dimensions, namely, the need to belong, the need for popularity, anxiety, and addiction. This research is descriptive quantitative research. The characteristics (criteria) of 200 participants in this study consisted of gender, age, and duration of access to TikTok per day. This scale was prepared through concept construction, item writing, item review, and validity and reliability tests. The construct-based validity test uses confirmatory factor analysis, and the reliability test uses internal consistency using Cronbach alpha and omega coefficients. This research produced a 12-item Fear of missing out (FOMO) behavioral scale with adequate psychometric properties in each behavioral dimension. This scale is expected to be a valid and reliable instrument to measure the level of FOMO in individual TikTok users. So, the scale can be used as a basis for developing intervention programs to overcome FOMO problems, especially for TikTok users. Even so, further research needs to be done with a more diverse sample to generalize the results of this study